CeCl3⋅7H2O-catalysed hydrophosphonylation of aldehydes and ketones: An expeditious route to α-hydroxyphosphonates under solvent-free conditions. (2nd December 2019) - Mahesh, R.; Sharma, Rupali; Kour, Parteek; Kumar, Anil
Abstract: A cerium(III) chloride-catalysed expeditious synthesis of α -hydroxyphosphonates via a modified Abramov synthetic protocol has been developed. The scope of the current protocol is broad, with a range of aromatic, α, β -unsaturated and heterocyclic aldehydes being efficiently converted to the anticipated products in very good to excellent yields (89–96%) in 15 min using low catalytic loading. The protocol was efficiently extended to hitherto unactivated cyclic ketones such as cyclopentanone and cyclohexanone to afford the required products in excellent yields. However, the reaction with cyclohexenone delivered a Michael product instead of the anticipated α -hydroxyphosphonates. The solvent-free conditions, low catalytic loadings, avoidance of toxic reagents and good to excellent yields are significant advantages of this protocol. Graphical Abstract: